The Design of a Hard Contact Lens Insertion Removal Device - Fakhouri, Abdulaziz S. (British Journal of Healthcare and Medical Research, 2025)
One of the most common types of vision diseases is refractive eye diseases, such as farsightedness and nearsightedness, which prevent light from properly getting focused on the retina, producing blurry images, and thus unclear vision. In the United States of America, over 150 million people suffer from refractive eye diseases, which prevent light from properly getting focused on the eye retina, producing blurry images, and thus unclear vision. In both refractive eye diseases, corneal curvature plays a crucial role in correctly focusing light on the retina. Keratoconus is a chronic disease of the corneal ectasia that affects the corneal curvature of the eye. Corneal ectasia is the gradual thinning of the cornea and expansion outward due to internal pressure, which makes the cornea shaped like a cone, affecting visual acuity due to astigmatism. Keratoconus usually affects around 1 in every 200,000 of the general population and affects children from the age of 10 years old. Mainly, the treatment of Keratoconus is either by stopping the progression of corneal ectasia or by improving vision, or both. Improving the vision could be done by utilizing hard contact lenses, yet they are difficult to insert into the eye and require skills. To reduce the difficulty of such a procedure, several devices were made to be utilized in the process of insertion or removal of the hard contact lenses. Yet, Users need adequate training and skills to use such devices correctly. There is a need for a device that combines most of the advantages of previously made devices, such as single-handed operation, safety, and ease of use, and avoids most of their disadvantages such as the risk in using loaded springs and eye trauma, not containing spilled lens solution, and operating with both hands. In this project, ideation sessions and concept selection were performed utilizing the Pugh method. A design of a hard contact lens insertion/ removal device was proposed utilizing 3D computer-assisted design (CAD) software. Five main parts were designed: the housing, the roller, the plunger bracket, the eyelid bracket, and the eyelid fasteners. Furthermore, an alpha phase prototype of the five parts was 3D printed and assembled utilizing computer-assisted manufacturing (CAM) as a proof of concept.